Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd004320.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Stapled versus handsewn methods for ileocolic anastomoses

Abstract: Stapled functional end to end ileocolic anastomosis is associated with fewer leaks than handsewn anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 33 publications
2
54
1
3
Order By: Relevance
“…Intraoperative problems and postoperative strictures seem to be more frequent in stapled anastomosis [118]. However, in a recent Cochrane review ileocolic stapler anastomoses were associated with fewer leaks than handsewn anastomoses [119]. …”
Section: Complicationsmentioning
confidence: 99%
“…Intraoperative problems and postoperative strictures seem to be more frequent in stapled anastomosis [118]. However, in a recent Cochrane review ileocolic stapler anastomoses were associated with fewer leaks than handsewn anastomoses [119]. …”
Section: Complicationsmentioning
confidence: 99%
“…Two of them were included in the systematic review (7,8) and one was a systematic review per se (9). With the additional search we selected more articles (10).…”
Section: Colorectal Surgerymentioning
confidence: 99%
“…The authors found no relevant clinical differences between the two methods, although intraoperative technical problems and postoperative strictures were more common with stapled anastomoses. A recent meta-analysis, published in Cochrane Library, focused on the outcomes after right colectomy and ileocolic anastomosis performed for right-sided colon cancer and Crohn's disease (9). Stapled anastomosis was associated with significantly fewer anastomotic leaks (1,4%), compared with the handsewn (6 %).…”
Section: Colorectal Surgerymentioning
confidence: 99%
“…Another recent study of 53 cases identified risk factors for dehiscence of stapled anastomoses, including the presence, duration, and number of intraoperative hypotensive periods, as well as colonic resection and anastomosis . Human patients with surgical indications for IRA, such as emergency general surgery, septic peritonitis, ileocolic anastomoses, or anastomoses in trauma patients have been proposed to benefit from selective techniques . The application of similar evidence‐based selective techniques in specific veterinary patients could reduce complications in companion animals.…”
Section: Introductionmentioning
confidence: 99%